Effect of Antisense Oligonucleotide to Annexin Ⅱ on the t—PA—mediated Plasminogen Activation in vitro - 张晓晖 周华荣 等 (Journal of Huazhong University of Science and Technology. Medical sciences, 2002)
In order to study the role of annexin Ⅱ,a recombinant expression vector,pZeoSV2(+)ANN II,containing the annexin II cDNA,was developed.The 1.1 -kb-length annexin II cDNA was inserted into a expression sector,PzeoSV(+) and transfected into HL-60 cells which had low baseline expression of Ann-II,pZeoSV(+) ANN II was analyzed by restriction mapping and the Ann-II sequence identified.The ability of the transfected cells,non-transfected and nock-transfected cells to stimulate t-PA-depend plasminogen activation was compared.The re-sults showed that HL-60 with pZeoSV(+) ANN II transfection could significantly increase the plasminogen activation(8.9±1.2U) in vitro with the difference being significant as compared with non-transfected(1.5±0.4U) and mock-transfected cells (4.2±0.9U),respectively.An-tiannexin II oligonucleotides significantly inhibited the binding ability of t-PA and plasminogen to annexin II ,and obviously reduced the plasminogen activation in vitro.The above findings showed human umbilical vein endothelial cells(HUVECs) treated with sense or missense oligonucleotides indicated no significant change in binding of t-PA and PLG.Treatment of HUVECs with antian-mexin II oligonucleotides could significantly reduce the plasminogen activation by 2.4±0.3 U as compared with sense oligonucleotide group in binding of t-PA and PLG.These results,therefore,suggest that Ann-II can bind plasminogen and participate in the stimulation of t-PA-dependent ac-tivation of plasminogen,and that interference with Ann-II mRNA by antisense oligonucleotide may be a new strategy for the therapy of bleeding in patients with hyperfibrinolysis.